2008
DOI: 10.1007/s11099-008-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence as a tool for evaluation of drought stress in strawberry

Abstract: The effect of water deficit on chlorophyll fluorescence, sugar content, and growth parameters of strawberry (Fragaria×ananassa Duch. cv. Elsanta) was studied. Drought stress caused significant reductions in leaf water potential, fresh and dry masses, leaf area, and leaf number. A gradual reduction of photochemical quenching (q P ) and quantum efficiency (Φ PS2 ) was observed under drought stress while non-photochemical quenching (q N ) increased. Maximum efficiency of photosystem 2 (F v /F m ) was not affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 12 publications
(12 reference statements)
4
38
1
3
Order By: Relevance
“…In the present work, the average values of potential quantum efficiency PS II (the parameter F v /F m ) were similar in the leaves of inbred and non-inbred plants. Similarly, R a z a v i et al [6] demonstrated in strawberry that maximum efficiency of photosystem II was not affected by drought stress.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In the present work, the average values of potential quantum efficiency PS II (the parameter F v /F m ) were similar in the leaves of inbred and non-inbred plants. Similarly, R a z a v i et al [6] demonstrated in strawberry that maximum efficiency of photosystem II was not affected by drought stress.…”
Section: Discussionmentioning
confidence: 87%
“…In the study by R a z a v i et al [6], the effect of water deficit on chlorophyll fluorescence, sugar content, and growth parameters of strawberry was investigated. A gradual reduction of photochemical quenching and quantum efficiency was observed under drought stress in strawberry cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous measurements of chlorophyll a fluorescence and gas exchange allow a better understanding of salt effects on the photosynthetic apparatus and have been very useful in the selection of plants more tolerant to adverse environmental conditions (Baker et al, 2008;Razavi et al, 2008;Lima Neto et al, 2014). In our study, in absence of NaCl, maize plants showed similar behavior even when submitted to pretreatment with H2O2.…”
Section: Resultsmentioning
confidence: 99%
“…However, because the F v /F m is hardly affected by mild drought stress or low irradiance (Baker and Rosenqvist, 2004;Razavi et al, 2008), the careful selection of an appropriate fluorescence parameter is important to evaluate the plant stress under the given environments. Furthermore, the value of F v /F m is dependent on the measurement of chlorophyll fluorescence emanated from only the top few layers of leaf chlorenchyma, whereas the oxidative damage occurs across the thickness of leaf (Maxwell and Johnson, 2000).…”
Section: Principal Component Analysismentioning
confidence: 99%